Combined effect of age and body mass index on postoperative mortality and morbidity in laparoscopic cholecystectomy patients - Fakhoury, Hana M. A.; Yousef, Ziad; Tamim, Hani; Daher, Sarah; Attasi, Abdul Aleem; Al Ajlan, Abdulaziz; Hajeer, Ali H. (Frontiers in Surgery, 2023)
Background: Previous studies have assessed the impact of age and body mass index (BMI) on surgery outcomes separately. This retrospective cohort study aimed to investigate the combined effect of age and BMI on postoperative mortality and morbidity in patients undergoing laparoscopic cholecystectomy.: Data from the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) database for laparoscopic cholecystectomy patients between 2008 and 2020 were analyzed. Patient demographics, functional status, admission sources, preoperative risk factors, laboratory data, perioperative variables, and 30-day postoperative outcomes were included in the dataset. Logistic regression was used to determine the association of age, BMI, and age/BMI with mortality and morbidity. Patients were stratified into different subcategories based on their age and BMI, and the age/BMI score was calculated. The chi-square test, independent sample t-test, and ANOVA were used as appropriate for each category.The study included 435,052 laparoscopic cholecystectomy patients. Logistic regression analysis revealed that a higher age/BMI score was associated with an increased risk of mortality (adj OR 13.13 95% CI, 9.19-18.77, p <0.0001) and composite morbidity (adj OR 2.57, 95% CI 2.23-2.95, p <0.0001).Older age, especially accompanied by a low BMI, appears to increase the post-operative mortality and morbidity risks in laparoscopic cholecystectomy patients, while paradoxically, a higher BMI seems to be protective. Our hypothesis is that a lower BMI, perhaps secondary to malnutrition, can carry a greater risk of surgery complications for the elderly. Age/BMI is strongly and positively associated with mortality and morbidity and could be used as a new scoring system for predicting outcomes in patients undergoing surgery. Nevertheless, laparoscopic cholecystectomy remains a very safe procedure with relatively low complication rates.